ACE-FTS observations of pyrogenic trace species in boreal biomass burning plumes during BORTAS - Tereszchuk, K. A.; González Abad, G.; Clerbaux, C.; Hadji-Lazaro, J.; Hurtmans, D.; Coheur, P.-F.; Bernath, P. F. (Atmospheric Chemistry and Physics, 2013)
To further our understanding of the effects of biomass burning emissions on atmospheric composition, the BORTAS campaign (BOReal forest fires on Tropospheric oxidants over the Atlantic using Aircraft and Satellites) was conducted on 12 July to 3 August 2011 during the boreal forest fire season in Canada. The simultaneous aerial, ground and satellite measurement campaign sought to record instances of boreal biomass burning to measure the tropospheric volume mixing ratios (VMRs) of short- and long-lived trace molecular species from biomass burning emissions. The goal was to investigate the connection between the composition and the distribution of these pyrogenic outflows and their resulting perturbation to atmospheric chemistry, with particular focus on oxidant species to determine the overall impact on the oxidizing capacity of the free troposphere. Measurements of pyrogenic trace species in boreal biomass burning plumes were made by the Atmospheric Chemistry Experiment Fourier Transform Spectrometer (ACE-FTS) onboard the Canadian Space Agency (CSA) SCISAT-1 satellite during the BORTAS campaign. Even though biomass burning emissions are typically confined to the boundary layer, outflows are often injected into the upper troposphere by isolated convection and fire-related convective processes, thus allowing space-borne instruments to measure these pyrogenic outflows. An extensive set of 14 molecules – CH3OH, C2H2, C2H6, C3H6O, CO, HCN, HCOOH, HNO3, H2CO, NO, NO2, OCS, O3, and PAN – have been analysed. Included in this analysis is the calculation of age-dependent sets of enhancement ratios for each of the species originating from fires in North America (Canada, Alaska) and Siberia for a period of up to 7 days. Ratio values for the shorter lived primary pyrogenic species decrease over time primarily due to oxidation by the OH radical as the plume ages and values for longer lived species such as HCN and C2H6 remain relatively unchanged. Increasing negative values are observed for the oxidant species, including O3, indicating a destruction process in the plume as it ages such that concentrations of the oxidant species have dropped below their off-plume values. Results from previous campaigns have indicated that values for the molar ratios of ΔO3 /ΔO obtained from the measurements of the pyrogenic outflow from boreal fires are highly variable and range from negative to positive, irrespective of plume age. This variability has been attributed to pollution effects where the pyrogenic outflows have mixed with either local urban NOx emissions or pyrogenic emissions from the long-range transport of older plumes, thus affecting the production of O3 within the plumes. The results from this study have identified another potential cause of the variability in O3 concentrations observed in the measurements of biomass burning emissions, where evidence of stratosphere–troposphere exchange due to the pyroconvective updrafts from fires has been identified. Perturbations caused by the lofted emissions in these fire-aided convective processes may result in the intrusion of stratospheric air masses into the free troposphere and subsequent mixing of stratospheric O3 into the pyrogenic outflows causing fluctuations in observed ΔO3/ΔCO molar ratios.